2009
DOI: 10.1007/s00244-009-9333-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Seafood Consumption on Urinary Excretion of Arsenic Species by Volunteers

Abstract: Arsenic (As) is a known human carcinogen and widely distributed in the environment. The main route of As exposure in the general population is through food and drinking water. Seafood harvested in Korea contains high-level organoarsenics such as arsenobetaine, arsenocholine, and arsenosugars, which are much less harmful than inorganic arsenics. However, for those who eat large amounts of seafood it is important to understand whether seafood consumption affects urinary levels of inorganic As metabolites such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…Ours and others studies had reported that DMA increased signiWcantly after seafood intake (Xu et al 2008a;Choi et al 2010). In this study, workers in two plants all consumed very little seafood during 3 days prior to the study period.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Ours and others studies had reported that DMA increased signiWcantly after seafood intake (Xu et al 2008a;Choi et al 2010). In this study, workers in two plants all consumed very little seafood during 3 days prior to the study period.…”
Section: Discussionmentioning
confidence: 67%
“…In occupationally exposed subjects, the urinary excretion of As metabolites varies in accordance with the dose absorbed from the working environment, but may also be inXuenced by other sources such as food and water. The food containing As is mainly seafood, which presents high concentration of organoarsenicals, such as arsenobetaine (Choi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ingested DMA and MA seem to be excreted mainly in urine in humans, and mostly within one day [49]. Our own and others data suggest that tAs ingested with seafood is eliminated from the body within approximately four days [93,107]. Upon 15 consecutive days with blue mussel consumption, a remarkably high 12 level of urinary MA was observed.…”
mentioning
confidence: 54%
“…From studies where humans have ingested seafood and the urinary excretion of arsenicals have been measured, no indications exist for formation of iAs from ingested organoarsenicals [46,49,54,85,93,99,100,143,144]. Scarce data from human seafood studies indicate that a repeated intake of seafood does not result in higher excretion of iAs than that ingested [93,107]. It is, however, not known whether urinary MA and DMA following seafood ingestion [54,93] are formed directly or via inorganic As intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is worthwhile to consider the potential role of AsB because it may influence other arsenic metabolites such as DMA (Francesconi et al, 2002). Recent studies have reported higher concentrations of DMA in individuals that have consumed fish or seafood during the days before urine sample collection (Choi et al, 2010;Fillol et al, 2010;Navas-Acien et al, 2011).…”
Section: Discussionmentioning
confidence: 99%